Fin geometry optimization for enhanced PCM solidification in solar cooking thermal storage system: Numerical simulation and experimental validation - Abraha Kahsay Kiros; Balewgize Amare Zeru; Debela Geneti Desisa; Desta Goytom Tewolde (International Journal of Thermofluids)
This study investigates the enhancement of heat transfer in phase change materials (PCMs) for solar cooking applications by optimizing fin dimensions to address the low thermal conductivity of PCM during the discharging process. A numerical and experimental analysis was conducted to evaluate the impact of fin length and thickness on solidification time and energy storage capacity, balancing the trade-off between heat transfer improvement and PCM volume reduction. Using ANSYS 16.0 for computational fluid dynamics (CFD) simulations and response surface methodology (RSM) for design optimization, the study employed solar salt (53 % KNO3, 6 % NaNO3, 41 % NaNO2) with a melting point of 142 °C and latent heat of 110 kJ/kg. Key parameters included fin lengths (70 - 140 mm) and thicknesses (0.8 - 1.5 mm), validated experimentally. Results demonstrated that increasing fin length significantly outperformed thickness enhancement; a fin with 1.5 mm thickness and 140 mm length reduced solidification time by 65.97 % compared to a finless system. RSM optimization identified a fin configuration of 0.8 mm thickness and 140 mm length as optimal, achieving complete solidification in 10.21 hours while releasing 2237.91 kJ of stored energy. These findings highlight the critical role of fin geometry in improving PCM efficiency, enabling effective solar energy storage for extended use, and advancing sustainable alternatives to conventional cooking fuels.